ANALYSIS ANTIOXIDANT ACTIVITY AND TOTAL FLAVONOID CONTENT COMBINATION OF ETHANOL EXTRACT OF KENCUR RHIZOME (Kaempferiae Galanga L.) AND TAPAK DARA LEAF (Catharanthus Roseus) USING DPPH METHOD: ANTIOXIDANT ACTIVITY - Galih Samodra; Linda Nur Azizah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Kaempferia galanga L and Catharanthus roseus leaves are natural ingredients that can be used as a source of antioxidants because they can reduce oxidative damage to the body due to free radicals. The aim of this research was to determine whether the ethanol extract of kencur rhizome and tapak dara leaves alone or combined has antioxidant properties that are able to fight free radicals. Methods: The method used to test antioxidant activity uses the DPPH (2,2-diphenyl-1 picrylhydrazyl) method. Results: the single ethanol extract of tapa dara leaves has antioxidant activity with an IC50 value of 32.17 ppm and is classified as very strong, while the single extract of kencur rhizome has antioxidant activity with an IC50 value of 17.30 ppm. and is classified as very strong. On the other hand, a mixture of ethanol extracts of tapak dara leaves and kencur rhizomes in a ratio of 1:2 showed very strong antioxidant activity, with an IC50 of 15.65 ppm. A mixture of tapak dara leaves and kencur rhizomes in a ratio of 2:1 showed very strong antioxidant activity with an IC50 value of 9.15 ppm. A mixture of galangal rhizome extract and tapak dara leaves in a ratio of 2:1 produces maximum antioxidant activity. This combination has very strong antioxidant activity compared to the individual forms of these compounds and is almost as strong as vitamin C which has an IC50 value of 5.30 ppm. Conclusion: : the combination of galangal rhizome extract and tapak dara leaves in a ratio of 2:1 produces very strong antioxidant activity compared to the single form of both.